The Impact of Reactive Routing Protocols for Transferring Multimedia Data over MANET - Abdullah, Ako Muhammad; Aziz, Roza Hikmat Hama (Sulaimani Journal for Pure and Applied Sciences, 2014)
A Mobile Ad-hoc Network (MANET) is a collection of wireless nodes that can be dynamically set up anytime and anywhere without requiring existing infrastructure. In the network each node works as a router to discover and maintain the routes form the source to destination. Nowadays, demanding for transferring multimedia traffic over MANET is increased while the different factors that effect in MANET to maintain real-time communication in the presence of a dynamic network topology. One of the factors that affect the ability of MANET to transfer multimedia traffic from source to destination is routing protocol. The main goal of this paper is the study, selection and evaluation the performance of two reactive routing protocols: Adhoc On Demand Distance Vector (ADOV) and Dynamic Source Routing (DSR) in a high mobility case under low, medium, and high density scenarios in order to transfer video conferencing application by using an OPNET simulator. While AODV and DSR share similar On Demand behavior, the protocols internal mechanism leads to significant differences in performance. The metrics used for performance analysis are average end-to-end delay, network load and throughput. As a result of our studies that the performance varies widely across different network sizes and results from once scenario cannot be applied to those from the other scenario. In all three scenarios, we concluded that performance of the DSR protocol is not good as throughput is very low and the routing load is very high when compared to AODV protocols. AODV exhibits a better performance than DSR protocols in terms of end-to-end delay. This study proves that AODV performs well in terms of end- to-end delay, network load, and throughput with increasing number of mobile nodes.
Keywords: Mobile Ad hoc Network; Ad hoc On Demand Distance Vector; Dynamic SourceRouting Protocol; Video Conferencing Application; Route Discovery and Route Maintenance